Expresión ¬a∨¬b∨¬c∨¬b∨(¬a∨¬¬b∨¬c∧¬¬a∨¬b∨¬c)∨¬a∧¬b
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
¬(¬b)=b¬(¬a)=a¬c∧¬(¬a)=a∧¬c(¬a∧¬b)∨(¬c∧¬(¬a))∨¬a∨¬b∨¬c∨¬(¬b)=1
Tabla de verdad
+---+---+---+--------+
| a | b | c | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 1 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 1 |
+---+---+---+--------+
| 1 | 0 | 1 | 1 |
+---+---+---+--------+
| 1 | 1 | 0 | 1 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+